2011
DOI: 10.1104/pp.110.171330
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Antibody Fragments with a ControlledN-Glycosylation Pattern and Induction of Endoplasmic Reticulum-Derived Vesicles in Seeds of Arabidopsis      

Abstract: Intracellular trafficking and subcellular deposition are critical factors influencing the accumulation and posttranslational modifications of proteins. In seeds, these processes are not yet fully understood. In this study, we set out to investigate the intracellular transport, final destination, N-glycosylation status, and stability of the fusion of recombinant single-chain variable fragments to the crystallizing fragment of an antibody (scFv-Fc) of two antiviral monoclonal antibodies (2G12 and HA78). The scFv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 67 publications
(106 reference statements)
7
50
0
Order By: Relevance
“…In transformant MBP39, an aberrant localization of the SSPs was observed (Van Droogenbroeck et al, 2007). However, this aberrant localization was not always penetrant and seems dependent of the growth conditions (Loos et al, 2011b), suggesting that there is no direct link between UPR induction and aberrant seed protein localization. It is also unlikely that the format of the antibody itself (VHH-Fc or scFv-Fc) triggers the UPR response, because VHH-Fc fusions do occur in different animal species and there is a high conservation between animal and plant ER folding and assembly.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In transformant MBP39, an aberrant localization of the SSPs was observed (Van Droogenbroeck et al, 2007). However, this aberrant localization was not always penetrant and seems dependent of the growth conditions (Loos et al, 2011b), suggesting that there is no direct link between UPR induction and aberrant seed protein localization. It is also unlikely that the format of the antibody itself (VHH-Fc or scFv-Fc) triggers the UPR response, because VHH-Fc fusions do occur in different animal species and there is a high conservation between animal and plant ER folding and assembly.…”
Section: Discussionmentioning
confidence: 96%
“…Immunolocalization studies on one of these scFv-Fcexpressing lines revealed an aberrant localization of the recombinant scFv-Fc, as well as of endoplasmic reticulum (ER) chaperone binding proteins (BiPs) and calreticulin, and of the endogenous SSP cruciferin, suggesting that the cellular homeostasis was disturbed. However, not all transformants, accumulating scFv-Fc antibodies in ER-derived vesicles, show this phenotype, indicating that also the environmental conditions of seed development and ripening affect the deposition of the recombinant protein (Van Droogenbroeck et al, 2007;Loos et al, 2011b). Similarly, interleukin-10 accumulated in compartments delimited by ribosome-associated membranes, which most likely derive from the ER (Morandini et al, 2011).…”
mentioning
confidence: 99%
“…Aberrant intracellular deposition and as a consequence, incorrect glycosylation of recombinant proteins are often reported. For example, recombinant proteins designed for secretion are frequently also located in the endoplasmic reticulum (ER) and as a consequence, carry oligomannosidic carbohydrates instead of the desired complex-type glycans (Loos et al, 2011;Schneider et al, 2014a). By contrast, KDEL-tagged proteins designed for ER retention are sometimes partially secreted (Van Droogenbroeck et al, 2007;Niemer et al, 2014).…”
mentioning
confidence: 99%
“…Alternatively, for parenteral application, the high protein concentration in desiccated seeds facilitates the downstream processing. Different full-length antibody and antibody formats, like ScFv, ScFv-Fc, VHHs and VHH-Fc, have been expressed effectively in seeds of both monocot and dicot plants (De Wilde et al, 2013, Khan et al, 2012, Loos et al, 2011b, Van Droogenbroeck et al, 2009, Virdi et al, 2013.…”
Section: In Seed Antibody Expressionmentioning
confidence: 99%